PROSPECTIVE ENGLISH LANGUAGE TEACHERS’ LEARNING STYLES - Tartila (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
Students have their preferences or styles of learning. To teach effectively, teachers need to consider these preferences because students’ learning style is one factor contributing to students’ success in learning. This paper aimed to identify and prepare information about students’ primary perceptual learning style preferences and minor learning preferences. I conducted research at the State Islamic University of Sulthan Thaha Saifuddin (UIN STS) Jambi. I elicited data using Reid’s (1987) Perceptual Learning Style Preferences (PLSP). The research findings show that the student’s primary perceptual learning style preferences were auditory (mean = 40.2). The minor perceptual learning style preferences were kinesthetic (mean = 37.0), visual (mean = 36.7), tactile (mean = 36.3), group (mean = 35.8), and individual (mean = 33.9).